Appropriateness of antimicrobial prescribing in a Swiss tertiary care hospital: a repeated point prevalence survey - Nicolas Gürtler; Andrea Erba; Céline Giehl; Sarah Tschudin-Sutter; Stefano Bassetti; Michael Osthoff (Swiss Medical Weekly, 2019)
AIMS OF THE STUDY